Desafios e potencialidades da operação e gerenciamento da Pousada Uacari pelas comunidades da RDS Mamirauá (AM) - Freire, Juliana Maria de Barros [UNIFESP] (2017)
This study is part of a research that involves the relationship between the local community of Mamirauá Sustainable Development Reserve (AM, Brazil) and the tourism practiced there. Since 1998, the Mamirauá Institute for Sustainable Development (IDSM) has been working together with local communities and the Association of Auxiliaries and Guides of Ecotourism of Mamirauá (AAGEMAM) advising them on the provision of tourist services at the Uakari Lodge, a Floting Eco lodge. The main concern of the project is the autonomy of communities in the management of the activity, generating employment and income, strengthening local governance and contributing to the conservation of natural resources. Nowadays, the IDSM is leading a process towards the transference of ownership and management of the lodge to the communities, paying close attention for this process can be sustainable and people are able to perform the economic management to conduct the business autonomously. Finding a legal/managerial model that strengthens the social arrangement and does not weaken it, that respects the productive chain established in there, and attend to the degree of social involvement that community members have with the project, can keep it successful. It is necessary to investigate local social relationships and a community perception about the business, so that it can subsidize the decisions about the appropriate model it will adopt. The present study intends to make a diagnosis of the challenges and possibilities of the transfer of the Uakari Lodge in the perceptions, expectations, wishes of the community members and managers of IDSM, elaborating with all these actors a new legal and business configuration more adapted to the complex local reality in order to guarantee business sustainability and its security. In order to meet the proposed objective, it was decided to carry out: 1) bibliographic review; 2) documentary analysis; 3) on-site observation in 3 field visits; 4) participatory observation of tourism activity; 5) Conversation Wheels (Focal Groups); 6) semi-structured interviews and 7) content analysis of collected testimonials; 8) a participatory decision-making workshop. The results obtained are presented in 3 stages: 1) qualitative and quantitative analysis of the content categories of the interviews and conversations in which became evident the four main groups of opinions about the transference (opposing community members, favorable community members, opposing IDSM members and favorable IDSM members) where the motives for the opinions range from: fear of business fail because of lack of capacity of community members (or its opposite: certainty of their capacity); desire to keep IDSM as a partner in the management (as owner and manager, or just as technical consultant); among others, less frequently mentioned. 2) creation of a preliminary report analyzing the most appropriate legal model for the transference (it was sent to all involved to support the decisions). The results of the content analysis along with the legal possibilities reported served as the basis for the final decision made in the stage 3) participatory decision-making workshop: the property with the Associação dos Produtores do Setor Mamirauá (APSM) (Association of the Producers of Mamirauá Sector) and the management with the AAGEMAM. Finally, all possible consequences of this experience for the development of public policies for Community-Based Tourism in Brazil are discussed in the final considerations of this study.